Consideraciones acerca del erotismo:en la investigación y en la poesía del siglo XVI - Schatzmann Willvonseder, Martin (Dicenda. Estudios de lengua y literatura españolas, 2003)
The first part of this article takes a historic review on the investigation of eroticism in XVIth century cancionero-poetry from the beginning as a serious subject of investigation and summarize bibliographically the most important publications of literary criticism, dictionaries and anthologies dedicated to the erotic subject. The second part compares definitions of amor and erotismo and sketches the expanse of the erotic love subject. It wants to open the vision limited by social and moral concepts of the moment inorder to be able to understand better the poetry of other centuries.